Dorsal scapular artery as a recipient vessel in the vessel‐depleted neck during free tissue transfer in head and neck reconstruction. Issue 7 (28th April 2017) - Rosko, Andrew J.; Ryan, Jesse T.; Wizauer, Eric J.; Ibrahim, Mohannad; Srinivasan, Ashok; Stucken, Chaz L.; Spector, Matthew E.
Abstract: Background: The vessel‐depleted neck poses a unique challenge to the microvascular surgeon. Using 3D modeling and cadaveric dissection, we describe the approach and advantages of a known but less frequently used recipient vessel, the dorsal scapular artery, during free tissue transfer. Methods: Three patients with vessel‐depleted necks required reconstruction with free tissue transfer. The dorsal scapular artery was used as a recipient vessel. Three‐dimensional anatomic models were created and cadaveric dissections were performed to characterize the anatomy. Results: The dorsal scapular artery was successfully used in 3 patients as the recipient pedicle for free tissue transfer. The vessel was identified deep in the posterior triangle after emerging through the brachial plexus. In all cases, the artery was in a previously undissected field, and had a large caliber and favorable geometry for microvascular anastomosis. Conclusion: The dorsal scapular artery is a viable recipient vessel during head and neck reconstruction in the vessel‐depleted neck.